2016
DOI: 10.1155/2016/4521807
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Uveal Melanoma: Methods, Applicability, and Limitations

Abstract: Animal models serve as powerful tools for investigating the pathobiology of cancer, identifying relevant pathways, and developing novel therapeutic agents. They have facilitated rapid scientific progress in many tumor entities. However, for establishing a powerful animal model of uveal melanoma fundamental challenges remain. To date, no animal model offers specific genetic attributes as well as histologic, immunologic, and metastatic features of uveal melanoma. Syngeneic models with intraocular injection of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 105 publications
(94 reference statements)
0
35
0
Order By: Relevance
“…Altogether, the data from primary or metastatic UM support the hypothesis that TAMs have pro-angiogenic and tumor-promoting activities in human UM. Accordingly, intraocular models of melanoma in syngeneic mice showed a tumor-promoting role of M2 type macrophages, particularly in aged mice [264, 265]. Indeed, depletion of macrophages strikingly inhibited intraocular melanoma growth in a syngeneic model [264] and, more recently, in a transgenic model of UM [266].…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, the data from primary or metastatic UM support the hypothesis that TAMs have pro-angiogenic and tumor-promoting activities in human UM. Accordingly, intraocular models of melanoma in syngeneic mice showed a tumor-promoting role of M2 type macrophages, particularly in aged mice [264, 265]. Indeed, depletion of macrophages strikingly inhibited intraocular melanoma growth in a syngeneic model [264] and, more recently, in a transgenic model of UM [266].…”
Section: Inflammationmentioning
confidence: 99%
“…Several transgenic mouse models of CM, which resemble the biological features of the human disease, also develop a choroidal melanoma, although they do not bear mutations typical of human UM [265]. Very recent studies exploited the activated GNAQ oncogene, which is found in a significant fraction of human UM, to develop transgenic UM models.…”
Section: Animal Modelsmentioning
confidence: 99%
“…One of the reasons might be the lack of reliable animal models to study the disease. To date, no spontaneous UM model has been established in mice . This might in part explain the difficulties to study the disease, particularly compared to cutaneous melanoma where transgenic mouse models are a cornerstone of preclinical analyses.…”
Section: Preclinical Approachesmentioning
confidence: 99%
“…New approaches aim to generate the spontaneous development of intraocular melanomas by crossbreeding of genetically engineered mice all of which have yet been unsuccessful. Most of the animal studies are done with xenograft animal models using immunosuppressed mice . Even though the eye is an immune‐privileged organ, tumor tumorigenesis and disease progression may be influenced by immune cells.…”
Section: Preclinical Approachesmentioning
confidence: 99%
“…These discoveries were largely enabled by the analysis of patient tumor specimens and have greatly advanced our understanding of the molecular underpinnings of uveal melanoma tumorigenesis and their prognostic significance. Various animal models have likewise been indispensable in elucidating the biology and potential therapeutic vulnerabilities of this cancer (Cao & Jager, ; Stei, Loeffler, Holz, & Herwig, ; Yang, Cao, & Grossniklaus, ). In the past several years, there have been many promising preclinical studies that have used these models to identify novel treatment strategies, several of which are now in the early stages of clinical trials (Vivet‐Noguer, Tarin, Roman‐Roman, & Alsafadi, ; Yang, Manson, Marr, & Carvajal, ).…”
Section: Introductionmentioning
confidence: 99%